1997
DOI: 10.1128/aac.41.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin, an active component of licorice roots, reduces morbidity and mortality of mice infected with lethal doses of influenza virus

Abstract: The antiviral effect of glycyrrhizin (GR), an active component of licorice roots, was investigated in mice infected with influenza virus A2 (H2N2). When mice that had been exposed to 10 50% lethal doses of the virus were treated intraperitoneally with 10 mg of GR per kg of body weight 1 day before infection and 1 and 4 days postinfection, all of the mice survived over the 21-day experimental period. At the end of this period, the mean survival time (in days) for control mice treated with saline was 10.5 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 27 publications
2
111
0
1
Order By: Relevance
“…An explanation of the beneficial effects of aspirin on the immune functions in the elderly is that this drug may ameliorate the inhibitory effects of prostaglandin E 2 (PGE 2 ) on lymphocyte and macrophage functions. ated by administration of Îł-IFN, further confirming a T-cell mediated phenomena being affected by glycyrrhizin (Utsunomiya et al, 1997).…”
Section: Other Natural Productsmentioning
confidence: 58%
See 1 more Smart Citation
“…An explanation of the beneficial effects of aspirin on the immune functions in the elderly is that this drug may ameliorate the inhibitory effects of prostaglandin E 2 (PGE 2 ) on lymphocyte and macrophage functions. ated by administration of Îł-IFN, further confirming a T-cell mediated phenomena being affected by glycyrrhizin (Utsunomiya et al, 1997).…”
Section: Other Natural Productsmentioning
confidence: 58%
“…Glycyrrhizin, which is present in liquorice roots and used in a number of traditional cough remedies, reduced the severity of infection in mice infected with influenza A H2N2 and reduced the lethality of the infection (Utsunomiya et al, 1997). This natural product did not affect virus replication in vitro but the protection appeared to be mediated by effects of this agent on T-cells.…”
Section: Other Natural Productsmentioning
confidence: 97%
“…18,19 In addition, GL has anti-viral capacity against herpes simplex virus, cytomegalovirus, and influenza virus. [20][21][22] However, Ito et al 23 reported that GL treatment did not influence the HCV viral load. Several reports also indicate that GL has immune-modulatory capacity.…”
Section: Discussionmentioning
confidence: 96%
“…Mice were prevented from lethal H2N2 infection by glycyrrhizin although no influence on virus replication was detected. The mechanism was suggested to be induction of interferon-c in T cells by glycyrrhizin [48]. In a recent report, glycyrrhizin reduced H3N2 titres in lungderived cells [28].…”
Section: Discussionmentioning
confidence: 98%